Research progress of dietary fiber in the role of chronic kidney disease - GAO Zhi-wei; LI Yang; WANG Zun-song (Linchuang shenzangbing zazhi)
Dietary fiber is known as the "seventh largest nutrient" following the traditional six nutrients,and is the essential nutrient for maintaining human nutrition and health.Studies in recent years have shown that dietary fiber intake can delay the progression of chronic kidney disease(CKD).This article reviews the definition and classification of dietary fiber,the physiological effect of dietary fiber,and its role in prevention and treatment of chronic kidney disease and its complications.